WORKLOAD AND JOB SATISFACTION OF UNIVERSITY STAFF IN LAGOS STATE, NIGERIA - Ayokunnu , Emmanuel Makanjuola; Afonja, A.F., Ph.D; Ememe, P. I., Ph.D (Journal of Continuing and Development Education, 2023)
Job satisfaction and workload in the world of work today are becoming paramount for effective delivery of service and performance. Work is an important aspect of human life that must be taken care of, and balance should be found between work, personal life, satisfaction and every other important aspects of man. This study, therefore, examined the relationship between workload and job satisfaction of university staff in Lagos State, Nigeria. The study adopted a descriptive survey research design as three research questions and hypotheses were developed to guide this study. The population of the study comprises all university staff in Lagos State, Nigeria. Purposive random sampling technique was used to select a foremost public university and a foremost private university in Lagos who’s both combined number of members of staff is 1,998. Taro Yamane sampling technique was used to select a sample size of 335 respondents out of the 1,998. Structured questionnaire was used as instrument for data collection and was validated by experts. The reliable co-efficient of 0.97 was obtained for the instrument. The data collected were analysed using descriptive and inferential statistics of chi square to test the hypotheses at 0.05 significance level. The outcome of the study revealed that there is a significant connection between workload and job satisfaction among university staff in Lagos State, Nigeria. The study concluded and recommended that HR managers, government and private university owners should try channeling workload towards positive behaviour and not to affect members of staff in a negative way; assessment should be done from time to time to avoid a situation whereby some members or units are overworking while some others are underworking; NUC should look into annual staff engagement and student enrolment in Nigerian universities, especially private universities to be able to find a balance in student-staff ratio in these institutions.